2021
DOI: 10.3389/fimmu.2021.656039
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil in Reverse Migration: Role in Sepsis

Abstract: Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. During the development and progression of sepsis, polymorphonuclear neutrophils (PMNs) are the most abundantly recruited innate immune cells at sites of infection, playing critical roles in the elimination of local infection and healing of the injury. PMN reverse migration (rM) describes the phenomenon in which PMNs migrate away from the inflammatory site back into the vasculature following the initial PMN infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…It is downregulated by iron-containing 2-oxoglutarate-dependent enzymes (abovementioned hydroxylases) having ascorbate as a cofactor [22]. As was mentioned by Ji and Fan [28], some studies revealed negative regulation of PMN rM with the suppressing role of HIF-1α, noted in zebrafish. Elks et al [33] with use of indirect HIF inhibitor, dimethyloxaloyglycine (DMOG) revealed that activated HIF-1α delays resolution of inflammation and it is a consequence of reduced neutrophil apoptosis and increased retention of these cells at the site of injury.…”
Section: Immunomodulation and Vitamin C As An Enzyme Cofactormentioning
confidence: 90%
See 1 more Smart Citation
“…It is downregulated by iron-containing 2-oxoglutarate-dependent enzymes (abovementioned hydroxylases) having ascorbate as a cofactor [22]. As was mentioned by Ji and Fan [28], some studies revealed negative regulation of PMN rM with the suppressing role of HIF-1α, noted in zebrafish. Elks et al [33] with use of indirect HIF inhibitor, dimethyloxaloyglycine (DMOG) revealed that activated HIF-1α delays resolution of inflammation and it is a consequence of reduced neutrophil apoptosis and increased retention of these cells at the site of injury.…”
Section: Immunomodulation and Vitamin C As An Enzyme Cofactormentioning
confidence: 90%
“…With the development of imaging technology, it has been found that the recruited polymorphonuclear leukocytes (PMNs) could migrate back to the circulation and it is a new way of PMN clearance in inflammatory or injury site. This process without undergoing apoptosis has been called as “PMN reverse migration (rM)” [ 28 ]. In 2004, Sharma et al [ 29 ] showed that after treatment of PMNs with E. coli or arachidonic acid, AA or DHA did not influence the phagocytosis of PMNs but improved ROS generation and apoptosis.…”
Section: Vitamin C and Its Mechanisms Of Immunomodulationmentioning
confidence: 99%
“…CXCL8 functions as a chemoattractant at lower concentrations, at higher concentrations, though, it acts as chemorepellent ( Tharp et al, 2006 ). In addition to these, other mechanisms have been proposed for reverse migration ( Elks et al, 2011 ; Nourshargh et al, 2016 ; Ji and Fan, 2021 ). Although an interesting and promising pathway, many questions remain unanswered in the process of reverse migration and more research must be conducted before we fully uncover the mechanistic details behind this orchestrated movement of neutrophils in the context of inflammation.…”
Section: Reverse Migrationmentioning
confidence: 99%
“…The ICAM1 high /CXCR1 low are long-lived with increased ROS levels and increased propensity to produce NETs ( Cerutti et al, 2013 ; Villanueva et al, 2011 ). Although the role of these rTM neutrophils can be both protective and tissue-damaging, but current studies suggest their detrimental roles in case of sepsis ( Ji and Fan, 2021 ), trauma, ischemia-reperfusion, and other chronic inflammatory diseases ( Hirano et al, 2016 ). Further studies need to be done to identify these rTM neutrophils in case of severe viral infections.…”
Section: Phenotypic Heterogeneity and Functional Versatility Of Neutrophilsmentioning
confidence: 99%